2008
DOI: 10.1172/jci32132
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of neural autoantigen in mouse liver suppresses experimental autoimmune neuroinflammation by inducing antigen-specific Tregs

Abstract: Tregs are important mediators of immune tolerance to self antigens, and it has been suggested that Treg inactivation may cause autoimmune disease. Therefore, immunotherapy approaches that aim to restore or expand autoantigen-specific Treg activity might be beneficial for the treatment of autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 44 publications
5
148
2
Order By: Relevance
“…Previous studies have shown that Tregs play a critical role in liver tolerance (13,22,23); however, in our study, Foxp3 + Treg numbers did not change in HBV-carrier mice, and CD25 + Treg depletion did not influence HBV persistence (Fig. S3).…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Previous studies have shown that Tregs play a critical role in liver tolerance (13,22,23); however, in our study, Foxp3 + Treg numbers did not change in HBV-carrier mice, and CD25 + Treg depletion did not influence HBV persistence (Fig. S3).…”
Section: Resultscontrasting
confidence: 71%
“…Furthermore, adoptive transfer of antigen-specific Tr1 cells induced an IL-10-dependent tolerance in the stringent mouse model of islet transplantation (11). The soluble peptide, myelin basic protein (MBP), could induce Ag-specific Tr1 cell generation, which plays a pivotal role in regulating T-cell tolerance that reverses ongoing experimental autoimmune encephalomyelitis disease in a rat model (12), which is consistent with the observation that MBP expression in mouse liver induces antigen-specific Tregs that protect from experimental autoimmune encephalomyelitis (13). Tr1 cells, in particular, are increased in the livers of patients with recurrent hepatitis C virus (HCV) infection after liver transplantation (14) and also mediate oral tolerance to BSA-induced systemic anaphylaxis (15).…”
supporting
confidence: 77%
“…For example, increased transgene expression from the AAV-8 vector correlated with a higher frequency of induced transgene productspecific Tregs, supporting the hypothesis that tolerance induction is facilitated by optimal induction of Tregs. While our published data indicated a requirement for Tregs in tolerance induction by hepatic gene transfer, others have shown that these cells may not only be required but sufficient to prevent certain types of immune responses (Cao et al, 2007a;Hoffman and Herzog, 2008;Luth et al, 2008).…”
Section: Optimal Hepatic Gene Transfer Reduces Impact Of Genetic Factmentioning
confidence: 73%
“…Induced Tregs were capable of suppressing cytotoxic T lymphocyte and antibody responses against F.IX, and were required for tolerance induction (Dobrzynski et al, 2006;Cao et al, 2007a). Once tolerance has been established, supplementary gene transfer to other organs or systemic therapeutic protein delivery can be safely applied (Hoffman et al, 2007;Passini et al, 2007;Sun et al, 2007;Luth et al, 2008). Tolerance induction by liver-restricted transgene expression has been documented for several different transgene products and vectors (Herzog, 2005;Brown et al, 2007;Cerullo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…By using the rAAV8 system used in clinical studies, we have recently provided proof of principle that overexpressing a single MHC molecule could lead to silencing of a primed, memory alloreactive response, leading to protection of a skin graft from rejection (14). Similar technology is already approved by the European Commission and European Medicines Agency for Glybera (rAAV1) and could potentially be extended for the induction of tolerance in autoimmune pathologic conditions (38).…”
Section: Discussionmentioning
confidence: 99%